2016
DOI: 10.1371/journal.pone.0158116
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Matrices on 3D-Cultured Prostate Cancer Cells' Drug Response and Expression of Drug-Action Associated Proteins

Abstract: This study investigated the effects of matrix on the behaviors of 3D-cultured cells of two prostate cancer cell lines, LNCaP and DU145. Two biologically-derived matrices, Matrigel and Cultrex BME, and one synthetic matrix, the Alvetex scaffold, were used to culture the cells. The cell proliferation rate, cellular response to anti-cancer drugs, and expression levels of proteins associated with drug sensitivity/resistance were examined and compared amongst the 3D-cultured cells on the three matrices and 2D-cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
40
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 84 publications
5
40
0
Order By: Relevance
“…Our data demonstrating the capability of viable GFs treated with high concentrations of TEGDMA to interact into 3D constructs versus their high mortality rate in 2D cultures highlighting the importance in the involvement of the 3D cell‐based ECM platform in the screening process of innovative materials and/or drugs. Studies performed on various cancer cells treated with anticancer drugs revealed a higher rate of survival for 3D‐matrigel versus 2D cultures (Edmondson, Adcock, & Yang, ). However, it should also be noted that the resistance is dependent on the cell type as no structural organization of DPMCs was observed at similar concentrations of TEGDMA (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Our data demonstrating the capability of viable GFs treated with high concentrations of TEGDMA to interact into 3D constructs versus their high mortality rate in 2D cultures highlighting the importance in the involvement of the 3D cell‐based ECM platform in the screening process of innovative materials and/or drugs. Studies performed on various cancer cells treated with anticancer drugs revealed a higher rate of survival for 3D‐matrigel versus 2D cultures (Edmondson, Adcock, & Yang, ). However, it should also be noted that the resistance is dependent on the cell type as no structural organization of DPMCs was observed at similar concentrations of TEGDMA (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…This could be explained by a proliferative capacity of the MDA-MB-231 cell line under these experimental conditions in comparison to the SUM1315 cell line that may exhibit a "stem-cell like" phenotype with slowed down proliferation rate [23]. In 3D culture models, cells forming spheroids may or may not proliferate according to cell type and the extracellular matrix environment [24,25]. Nevertheless, in both TNBL 3D cell cultures, spheroid diameters did not exceed 1000 μm, which could be explained by the fact that the spheroids had reached their growth plateau [19].…”
Section: Discussionmentioning
confidence: 99%
“…Microtubules are dynamically regulated by polymerization and depolymerization, and their mechanical properties determine their own shape and strength . Besides, βIII‐tubulin protein that is encoded by TUBB3 is upregulated in prostate cancer cells under 3D culture conditions compared to 2D culture condition and elevated expression of βIII‐tubulin may associate with the resistance to microtubule inhibitor docetaxel . Thus, TUBB3 may contribute to spheroid formation of bladder CSCs through modulating microtubule activity.…”
Section: Discussionmentioning
confidence: 99%